Knowledge diffusion and industry growth: The case of Japan's early cotton spinning industry - Serguey Braguinsky (Osaka University, Institute of Social and Economic Research (ISER), 2015)
The diffusion of technological knowledge is key to industry growth. But not all knowledge is created equal. I use a nanoeconomic approach to examine knowledge-diffusion based growth in the Meiji-era Japanese cotton spinning industry, which enjoyed remarkable success after a decade of initial failure. By tracing sources of technological knowledge to individual engineers, I find that successful technology diffusion required the right kind of human capital embodying and transmitting knowledge, and a competitive environment that rewarded talent while weeding out incompetence.
Keywords: O33; O14; 330